Promoting electrocatalytic CO2 reduction to formate via sulfur-boosting water activation on indium surfaces - Wenchao Ma (Nature Portfolio, 2019)
CO2 conversion to liquid fuels provides an appealing means to remove the greenhouse gas, although it is challenging to find materials that are both active and selective. Here, authors show sulfur-doped indium to be a highly active and selective electrocatalyst that transforms CO2 into formate.